2018
DOI: 10.18632/oncotarget.26189
|View full text |Cite
|
Sign up to set email alerts
|

The Cockayne syndrome protein B is involved in the repair of 5-AZA-2′-deoxycytidine-induced DNA lesions

Abstract: The Cockayne Syndrome Protein B (CSB) plays an essential role in Transcription-Coupled Nucleotide Excision Repair (TC-NER) by recruiting repair proteins once transcription is blocked with a DNA lesion. In fact, CSB-deficient cells are unable to recover from transcription-blocking DNA lesions. 5-Aza-2′-deoxycytidine (5-azadC) is a nucleoside analogue that covalently traps DNA methyltransferases (DNMTs) onto DNA. This anticancer drug has a double mechanism of action: it reverts aberrant hypermethylation in tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Similarly, treatment with aphidicolin reduces chromosome damage following exposure to 5-azadC, an inhibitor of DNA methyltransferase 1 (DNMT1), suggesting that trapping of DNMT1 at replication forks leads to replication fork collapse [ 136 ]. Increased levels of DNA damage have been observed in CSB-deficient cells exposed to 5-azadC, which is thought to be due to a failure in CSB-mediated TC-NER, leading to increased replication stress [ 64 ]. The synergistic sensitivity observed in a panel of acute myeloid leukemia (AML) cells exposed to olaparib and 5-azadC has been ascribed to a failure to repair the 5-azadC-induced lesions through BER [ 137 ], which could also be a mechanism behind the sensitivity of CSB-deficient cells to this drug since CSB also plays a role in BER.…”
Section: Csb and Its Implications In Targeted Therapy In Cancermentioning
confidence: 99%
“…Similarly, treatment with aphidicolin reduces chromosome damage following exposure to 5-azadC, an inhibitor of DNA methyltransferase 1 (DNMT1), suggesting that trapping of DNMT1 at replication forks leads to replication fork collapse [ 136 ]. Increased levels of DNA damage have been observed in CSB-deficient cells exposed to 5-azadC, which is thought to be due to a failure in CSB-mediated TC-NER, leading to increased replication stress [ 64 ]. The synergistic sensitivity observed in a panel of acute myeloid leukemia (AML) cells exposed to olaparib and 5-azadC has been ascribed to a failure to repair the 5-azadC-induced lesions through BER [ 137 ], which could also be a mechanism behind the sensitivity of CSB-deficient cells to this drug since CSB also plays a role in BER.…”
Section: Csb and Its Implications In Targeted Therapy In Cancermentioning
confidence: 99%
“…Although initially surprising, the ability of single agent 5-aza-dC to induce PARP1-DNA adducts is readily explained in the context of the known activities of 5-aza-dC, DNMT1 and PARP1. Incorporation of 5-aza-dC can induce DNA damage, either directly or as a result of aberrant repair of the normally transient covalent DNA adducts formed by DNMT1 (Juttermann et al, 1994;Jackson-Grusby et al, 1997;Palii et al, 2008;Maslov et al, 2012;Orta et al, 2013;Orta et al, 2014;Jeltsch and Jurkowska, 2016;Burgos-Moron et al, 2018). Depletion of DNMT1 protected K562 and GM369 cells from 5-aza-dC, indicating that DNMT1 adducts contribute significantly to 5-aza-dC cytotoxicity in both cell types.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage results from 5-aza-dC treatment, as evidenced by mutations and genomic instability in surviving cells (Juttermann et al, 1994;Jackson-Grusby et al, 1997;Palii et al, 2008;Maslov et al, 2012;Orta et al, 2013;Orta et al, 2014;Burgos-Moron et al, 2018). A multiprotein complex including not only DNMT1 but also PARP1 responds to damage requiring replicative repair (O'Hagan et al, 2011;Muvarak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1-DPCs could cause the block of DNA replication forks, leading to SSBs and DSBs that provoke cell death if not repaired . Recent studies have revealed a Cockayne syndrome protein B (CSB)-dependent transcription-coupled nucleotide excision repair (TC-NER) pathway to repair 5-azadC-induced DNMT1-DPCs . However, it is unclear if TC-NER is the sole mechanism to remove DNMT1-DPCs or other repair pathways are also involved.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recent studies have revealed a Cockayne syndrome protein B (CSB)-dependent transcription-coupled nucleotide excision repair (TC-NER) pathway to repair 5-azadC-induced DNMT1-DPCs. 24 However, it is unclear if TC-NER is the sole mechanism to remove DNMT1-DPCs or other repair pathways are also involved. In addition, the details of the proteolytic process in the repair of DNMT1-DPCs, which is believed to be the universal step to initiate DPC-repair, have not yet been clarified.…”
Section: ■ Introductionmentioning
confidence: 99%